Gender‐related differences in hospitalized heart failure patients. (July 2013) - Stein, Gideon Y.; Ben‐Gal, Tuvia; Kremer, Angelika; Bental, Tamir; Alon, Danny; Korenfeld, Roman; Yedidia, Idit; Porter, Avital; Abramson, Evgeny; Sagie, Alexander; Fuchs, Shmuel
<x xml:space="preserve">Abstract</x> Aims The burden of heart failure (HF)‐related hospitalization and mortality of female patients with HF is substantial. Currently, several gender‐specific distinctions have been recognized amongst HF patients, but their relationships to outcomes have not been fully elucidated. Accordingly, in the current work, we aimed to explore gender‐specific clinical and echocardiographic measures and to assess their potential impact on outcome. Methods and results We studied all consecutive HF patients, aged 50 or older, who had been hospitalized between January 2000 and December 2009, and had undergone at least one echocardiography study. A comparative analysis of clinical and echocardiographic findings was performed between 5228 males and 4107 females. Patients were followed for a mean of 2.8 ± 2.6 years. Females compared with males had less ischaemic heart disease, prior stroke, chronic renal failure, and COPD, and higher rates of hypertension, AF, obesity, valvular abnormalities, and pulmonary hypertension. Unadjusted 30‐day and 1‐year mortality rates were higher among women, while age‐adjusted rates were similar. Predictors of outcomes varied between genders. Female‐specific predictors of mortality included aortic stenosis, pulmonary hypertension, and malignancy, whereas diastolic dysfunction and chronic renal failure were found to be male‐specific predictors. Conclusions Age‐adjusted mortality rates of male and female hospitalized HF patients are similarly high. Predictors of mortality, however, are gender distinctive, and these measures may allow a better identification of high‐risk HF patients.